Internet Voting Protocols: An Analysis of the Cryptographic Operations per Phase - Satizabal, Cristina; Paez, Rafael (International Journal of Communication Networks and Information Security (IJCNIS), 2022)
Internet voting is a good option for Colombia thanks to the expansion of mobile technology throughout the country and the interest of the government to implement the e-voting. For this reason, we study the e-voting protocols to establish if any of them is suitable for Colombian elections. However some of them imply a great number of cryptographic operations and therefore a great computational cost for the devices, which sometimes exceed their capacity. In this paper, we determine the number of cryptographic operations per phase of four e-voting protocols: one based on blind signatures (Li, Hwang and Lai protocol), one based on mix nets (Meng protocol), one based on homomorphic encryption (EVIV protocol) and one used in real electoral processes (I-Voting for Estonian Elections). Then, we analyze the changes in the number of operations when the number of voters, number of votes, number of authorities and number of candidates increase for small, medium and large elections. Finally, we establish the protocol that imply a less number of cryptographic operations and is suitable for big electoral processes, such as congress elections in Colombia.